Driving resumption after critical illness:A survey and framework analysis of patient experience and process. (February 2023) - Meyer, Joel; Pattison, Natalie; Apps, Chloe; Gager, Melanie; Waldmann, Carl
Background: Adverse sequelae are common in survivors of critical illness. Physical, psychological and cognitive impairments can affect quality of life for years after the original insult. Driving is an advanced task reliant on complex physical and cognitive functioning. Driving represents a positive recovery milestone. Little is currently known about the driving habits of critical care survivors. The aim of this study was to explore the driving practices of individuals after critical illness. Methods: A purpose-designed questionnaire was distributed to driving licence holders attending critical care recovery clinic.Results: A response rate of 90% was achieved. 43 respondents declared their intention to resume driving. Two respondents had surrendered their licence on medical grounds. 68% had resumed driving by 3 months, 77% by 6 months, and 84% by 1 year. The median interval (range) between critical care discharge and resumption of driving was 8 weeks (1–52 weeks). Psychological, physical and cognitive barriers were cited by respondents as barriers to driving resumption. Eight themes regarding driving resumption were identified from the framework analysis under three core domains and included: psychological/cognitive impact on ability to drive (Emotional readiness and anxiety; Confidence; Intrinsic motivation; Concentration), physical ability to drive (Weakness and fatigue; Physical recovery), and supportive care and information needs to resume driving (Information/advice; Timescales). Conclusion: This study demonstrates that resumption of driving following critical illness is substantially delayed. Qualitative analysis identified potentially modifiable barriers to driving resumption.